Controlled drug delivery systems - Opara, Emmanuel C. (Boca Raton : CRC Press, 2020)
"This book will describe current research on drug delivery systems that encompass four broad categories, namely: routes of delivery, delivery vehicles, payload, and targeting strategies"--Provided by publisher.
Introduction : Approaches to controlled drug delivery / Antonios Mikos -- Chemical modifications of alginate for controlled drug delivery and regenerative medicine / Mark E. Welker -- Hydrogel systems for delivery and release of cell-secreted and synthetic therapeutic products / Aleks Skardal -- The effect of glutathione incorporated as chain transfer agent in thermo-sensitive hydrogels for controlled release of therapeutic proteins / V Perez-Luna -- Controlled vaccine delivery / Kevin McHugh -- Controlled release of hormone by pellet implants / Sivanandane Sittadjody -- Delivery of ovarian hormones for bone health / Justin Saul -- Controlled delivery models of bioactive factors for the maturation of engineered tissues / Ashkan Shafiee & Atala -- Controlled delivery of angiogenic proteins / Eric M Brey -- Controlled therapeutic delivery in wound healing / Sean Murphy -- Leveraging plasma insulin estimates and wearable technologies to develop an automated insulin delivery system in Type 1 diabetes / A Cinar -- New developments in oral insulin delivery / Emmanuel C Opara -- Insulin delivery by a bioartficial pancreas / Will Kendall -- Transdermal drug delivery / Brahmeshwar Mishra -- Mucoadhesive chitosan-based nanoparticles for oral drug delivery / Shirui Mao -- Liposome-based delivery of therapeutic agents / Eneida de Paula -- Targeted intestinal delivery of probiotics / Emmanuel C. Opara.
OCLC-licensed vendor bibliographic record.
Keywords: Drug delivery systems; MEDICAL / Pharmacology; MEDICAL / Pharmacy